DNA origami-based shape IDs for single-molecule nanomechanical genotyping - Zhang, Honglu; Chao, Jie; Pan, Dun; Liu, Huajie; Qiang, Yu; Liu, Ke; Cui, Chengjun; Chen, Jianhua; Huang, Qing; Hu, Jun; Wang, Lianhui; Huang, Wei; et al. (Nature communications, 2017)
Variations on DNA sequences profoundly affect how we develop diseases and respond to pathogens and drugs. Atomic force microscopy (AFM) provides a nanomechanical imaging approach for genetic analysis with nanometre resolution. However, unlike fluorescence imaging that has wavelength-specific fluorophores, the lack of shape-specific labels largely hampers widespread applications of AFM imaging. Here we report the development of a set of differentially shaped, highly hybridizable self-assembled DNA origami nanostructures serving as shape IDs for magnified nanomechanical imaging of single-nucleotide polymorphisms. Using these origami shape IDs, we directly genotype single molecules of human genomic DNA with an ultrahigh resolution of ∼10 nm and the multiplexing ability. Further, we determine three types of disease-associated, long-range haplotypes in samples from the Han Chinese population. Single-molecule analysis allows robust haplotyping even for samples with low labelling efficiency. We expect this generic shape ID-based nanomechanical approach to hold great potential in genetic analysis at the single-molecule level. Atomic force microscopy allows for the imaging of molecules at a nanometre resolution. Here the authors combine AFM with self-assembling DNA origami structures to detect single-nucleotide polymorphisms and determine haplotypes.